2021
DOI: 10.4240/wjgs.v13.i6.585
|View full text |Cite
|
Sign up to set email alerts
|

Chylous ascites in colorectal surgery: A systematic review

Abstract: BACKGROUND Chylous ascites is a rare complication in colorectal surgery with limited evidence. AIM To systematically review all available evidence to describe the incidence, clinical presentation, risk factors and management strategies. METHODS The systematic review was performed through PubMed, MEDLINE, EMBASE and Cochrane and cross-checked up to November 2020. The data collated included: Demographics, indications (benign vs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…A systematic review concluded that a chylous ascites diagnosis is often based on appearance in the drainage tube, and the inclusion of drainage volume (≥200 mL/d) and triglyceride levels (≥110 mg/ dL) is controversial because of a lack of criteria. 9 Determining the criteria for chylous ascites will be an important aim in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A systematic review concluded that a chylous ascites diagnosis is often based on appearance in the drainage tube, and the inclusion of drainage volume (≥200 mL/d) and triglyceride levels (≥110 mg/ dL) is controversial because of a lack of criteria. 9 Determining the criteria for chylous ascites will be an important aim in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that risk factors for chylous ascites in colorectal surgery include right-sided colon cancer, the number of dissected lymph nodes, and a shorter operative time. [7][8][9][14][15][16] However, few studies have focused only on left-sided colon and rectal lesions, and none have examined the relationship between lymphatic sealing around the IMA and chylous ascites.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations